Financial Risk Management. - Schönborn, Jana (Diplomica Verlag, 2010)
HauptbeschreibungAfter risk management and interest risk management in particular was primarily relevant for banks in the past, it is a crucial competition factor for all enterprises today. With increasing volatile financial markets and global competition CFOs are focusing more and more on an efficient measurement and management of interest rate risk. In this context this book aims to point out the risks of an adverse change in interest rates for a corporate portfolio of interest-bearing positions and show possibilities to measure and manage these risks. First the scene for interest risk manage.